Genome-wide characterization and expression analysis of the Dof gene family related to abiotic stress in watermelon - Zhou,Yong; Cheng,Yuan; Wan,Chunpeng; Li,Jingwen; Yang,Youxin; Chen,Jinyin (PeerJ, 2020)
The plant DNA-binding with one finger (Dof) gene family is a class of plant-specific transcription factors that play vital roles in many biological processes and stress responses. In the present study, a total of 36 ClDof genes were identified in the watermelon genome, which were unevenly distributed on 10 chromosomes. Phylogenetic analysis showed that the ClDof proteins could be divided into nine groups, and the members in a particular group had similar motif arrangement and exon–intron structure. Synteny analysis indicated the presence of a large number of syntenic relationship events between watermelon and cucumber. In promoter analysis, five kinds of stress-related and nine kinds of hormone-related cis-elements were identified in the promoter regions of ClDof genes. We then analyzed the expression patterns of nine selected ClDof genes in eight specific tissues by qRT-PCR, and the results showed that they have tissue-specific expression patterns. We also evaluated the expression levels of 12 selected ClDof genes under salt stress and ABA treatments using qRT-PCR. As a result, they showed differential expression under these treatments, suggesting their important roles in stress response. Taken together, our results provide a basis for future research on the biological functions of Dof genes in watermelon.
Keywords: Watermelon; Dof; Phylogenetic analysis; Expression profile; Abiotic stress